Pencegahan Penyakit Hipertensi Melalui Penyuluhan Kesehatan dan Pelatihan Pengukuran Tekanan Darah Pada Kader PKK - Riskiyah; Ermin Rachmawati (Ilin Institute, 2021)
The purpose of providing health counseling related to hypertension and blood pressure measurement training to pkk mother cadres during the pandemic is expected to increase their knowledge about hypertension disease and its prevention so that it can be applied to the family as well as to the community and can conduct independent blood pressure checks to other family members. This activity was carried out twice, namely in August and September 2020, to the Cadre of PKK Mother Semanding Hamlet, Sumber Sekar Village, Dau District, Malang Regency, a total of 27 people. The first activity in the form of health counseling is carried out by lecture methods and media in power points and leaflets. The materials provided are related to understanding clinical symptoms, complications, risk factors, prevention, a hypertensive diet with a DASH diet. or blood pressure training by simulation method and self-practice. The second activity is a blood pressure test of participants and TABATA gymnastics. Evaluation of this activity is done by analyzing participants' pretest and post-test values before and after counseling. The evaluation results obtained, there is a change in the level of knowledge of participants related to hypertensive disease and its prevention. This can be seen from the increase in posttest value and the decrease in standard deviation after counseling. In addition, the signification value of <0,000 indicates that this counseling is effective in increasing knowledge for PKK cadres.